An Analysis of Students’ Reading Interest in Journal Articles - Hermaya Anggraeni; Yohanes Gatot Sutapa Yuliana; Sumarni (ETERNAL (English Teaching Journal), 2024)
This research aims to determine the level of reading interest and the factors that influence the reading interest of fifth-semester students of the English Education Study Program at Tanjungpura University in reading journal articles. The research method in this research is qualitative research. Data was obtained through questionnaires and interviews. The questionnaire is to determine the level of students' reading interest in English language journal articles; the interview is to obtain more in-depth information regarding students' reading interest in English language journal articles. The population in this study consisted of 50 fifth-semester students, all of whom were also included in the sample, with five of these students selected as interview informants. From the research results, the authors discovered that 24 respondents (48%) got the "Very High" category, 19 respondents (38%) got the "High" category, and 7 respondents (14%) got the "Enough" category. Meanwhile, research results from interviews included five factors that influenced students' reading interest in English journal articles. These factors include Eligibility in Reading Journal Articles, Student's Willingness to Read Journal Articles, Journal Articles as Reading Materials, Benefits of Reading Journal Articles, and Benefits for Language Proficiency.